Low-Dose Aspirin Thromboprophylaxis Is Safe and Effective in Patients Undergoing Total Hip Arthroplasty with or without Outpatient Pneumatic Compression Devices - Tang, Alex; Lygrisse, Katherine A.; Zak, Stephen G.; Hepinstall, Matthew S.; Slover, James D.; Long, William J.; Schwarzkopf, Ran; Macaulay, William (The Journal of Hip Surgery, 2021)
Venous thromboembolism (VTE) remains a serious complication following total hip arthroplasty (THA). Current guidelines recommend pharmacologic prophylaxis with or without intermittent pneumatic compression devices (IPCDs). At our institution, portable IPCDs were previously worn by THA patients at standard risk for VTE for 14 days. Routine prescription of portable outpatient IPCDs was discontinued due to concerns with their efficacy and safety. We sought to determine if discontinuation of portable outpatient IPCDs changed VTE rates after THA. A retrospective review of 1,825 consecutive THA cases was conducted identifying patients with VTE, periprosthetic fractures, dislocations, bleeding complications, infection, and death at 90 days postoperatively. Patients were divided into two cohorts. One cohort received outpatient IPCDs for a period of 14 days (control) while the other did not (no-IPCD). All patients received inpatient IPCDs and were maintained on 81-mg aspirin (ASA) twice daily for 28 days. A total of 748 IPCD patients and 1,077 no-IPCD patients were identified. There was no difference between the total VTE rate for the IPCD versus no-IPCD groups (0 vs. 0.19%, p = 0.24). There were also no differences in periprosthetic fractures (p = 0.09), dislocations (p = 0.22), bleeding complications (p = 0.79), or infection rates (p = 0.75). No deaths were observed. The use of a low-dose ASA thromboprophylaxis protocol was safe and effective for VTE prevention in standard-risk patients undergoing THA with or without portable IPCDs. Any marginal benefit of portable IPCD use was too small to demonstrate despite our relatively large sample size.
Keywords: aspirin; VTE prophylaxis; outpatient intermittent pneumatic compression devices; primary total hip arthroplasty